IMPLEMENTASI MANAJEMEN WAKTU DALAM MENINGKATKAN KEDISIPLINAN PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMP ISLAM SALSABILA - -, Rizky Ananda Putri; Eneng Muslihah; Wahyu Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study highlights the importance of implementing effective time management in improving the discipline of teachers and educational staff at SMP Islam Salsabila. Using a qualitative research method with a case study approach, this study evaluates the impact of time management on discipline through observation, interviews and document analysis related to time management practices in the school. The findings show that strategies such as daily planning, prioritisation and structured breaks help teachers to complete tasks more efficiently, reduce tardiness and increase work productivity. Proper implementation of time management also creates a more conducive working environment, supports a consistent culture of discipline and increases professionalism in the performance of daily tasks. These findings not only contribute to improved individual performance, but also have a positive impact on the quality of education in the institution. Therefore, the results of this study are expected to serve as a reference for other educational institutions in developing more effective time management policies to improve teachers discipline, productivity and quality of work, so that educational goals can be better achieved.